The impact of computerization on the reference library staff of four university libraries in Metro Manila - Ontiveros, Irene P.; Dizon, Leticia B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
The purpose of this study is to assess the impact of computerization specifically on the reference library staff of four university libraries in Metro Manila, i.e., UP Diliman Main Library, Ateneo de Manila University Library, De La Salle University Library and University of Santo Tomas Library. The impact assessment method developed by the International Development Research Centre (IDRC) was used. However, only three out of five IDRC assessment indicators were used, i.e., performance, effectiveness and impact. Twenty-six library staff of the four university libraries responded to a structured questionnaire.
The major findings of the study are: (1) More than half (54) of the library staff had positive feelings on the use of computers and 38 percent had mixed feelings; (2) More than half (54) viewed computerization as having only positive effects and 38 percent as having both positive and negative effects; (3) The OPAC and CD-ROMs increased the tasks of the library staff. The library staff believe that assistance to users and looking for materials using OPAC and CD-ROMs were the tasks added; (4) The use of the card catalog and the printed form of reference tools decreased; (5) Computerization did not affect the job satisfaction of the library staff; (6) The main cause of job satisfaction before computerization was that the library staff could give assistance to users. The main cause of job satisfaction after computerization was the improvement of the quality of reference service; (7) There was a decrease in the length of the reference service time from 6-10 minutes to 1-5 minutes; (8) After computerization, the cost of the reference services decreased by as much as 80 percent.
Overall, computerization had a positive impact on the jobs of the academic reference library staff. The library staff also enjoyed their jobs with the introduction of computers.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- automation; Library employees -- Philippines -- Manila Metropolitan Area; Reference services (Libraries) -- Philippines -- Manila Metropolitan Area